2012
DOI: 10.4269/ajtmh.2012.11-0471
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro and In Vivo Studies of the Trypanocidal Activity of Four Terpenoid Derivatives against Trypanosoma cruzi

Abstract: Abstract. Four terpenoid derivatives were examined for their activity against Trypanosoma cruzi. Our results show that two compounds were very active in vitro against both extra-and intracellular forms. These compounds, non-toxic for the host cells, are more effective than the reference drug benznidazole. The capacity to infect cells was negatively affected and the number of amastigotes and trypomastigotes was reduced. A wide range of ultrastructural alterations was found in the epimastigote forms treated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 38 publications
0
14
0
Order By: Relevance
“…Among the natural compounds, terpenoids display a wide range of biological activities such as anticancer and anti-inflammatory actions and are effective against infective agents such as viruses, bacteria and parasites [10], [11]. Several terpenoids have been reported to have trypanocidal and leishmanicidal activities [12][15]. Recent research has shown the potential role of terpenoids as promising compounds against neglected protozoan diseases such as Chagas' disease and leishmaniasis [16], [17].…”
Section: Introductionmentioning
confidence: 99%
“…Among the natural compounds, terpenoids display a wide range of biological activities such as anticancer and anti-inflammatory actions and are effective against infective agents such as viruses, bacteria and parasites [10], [11]. Several terpenoids have been reported to have trypanocidal and leishmanicidal activities [12][15]. Recent research has shown the potential role of terpenoids as promising compounds against neglected protozoan diseases such as Chagas' disease and leishmaniasis [16], [17].…”
Section: Introductionmentioning
confidence: 99%
“…2015) and terpenoids (Ramírez-Macías et al . 2012; Lozano et al . 2016) were the main classes of secondary metabolites associated with antitrypanosomal activity in both diseases.…”
Section: Discussionmentioning
confidence: 99%
“…The oxidation yield was 97%; 13 3-O-Succinyl-11-oxo-α/β-amyrin (7) A solution of 3-O-succinyl-α/β-amyrin (0.20 g, 0.380 mmol), acetic anhydride (3 mL) and acetic acid tert-butyl chromate (3 mL) was refluxed for 6 h. The mixture was concentrated and subjected to liquid-liquid extraction with CH 2 Cl 2 /H 2 O and oxalic acid (5%). The oxidation yield was 97%; 3-O-Phthaloyl-11-oxo-α/β-amyrin (8) To obtain the solution of 3-O-phthaloyl-11-oxo-α/β-amyrin (8), acetic anhydride (3 mL) and acetic acid tert-butyl chromate (3 mL) were added in the 3-O-phthaloyl-α/β-amyrin (0.20 g, 0.348 mmol), and refluxed for 6 h. Then, the mixture was concentrated and subjected to liquid-liquid extraction with CH 2 Cl 2 /H 2 O and oxalic acid (5%).…”
Section: -O-phthaloyl-α/β-amyrin (5)mentioning
confidence: 97%
“…Then, isopropanol (2 mL) was added and, after 10 min, the product was washed with aqueous solution of oxalic acid (10%, 3 × 10 mL) and water (3 × 10 mL), dried with sodium sulfate (Na 2 SO 4 ) and the solvent evaporated, under vacuum. The product (85 mg) was subjected to separation by semi-preparative HPLC, thus obtaining a white solid (10 mg), which was characterized as lup-20(29)-en-3-one; 13 C NMR (100 MHz, CDCl 3 ) was compared with literature data. Betulinic acid (11) This natural compound was previously isolated and characterized by our collaborator from Gustavia augusta L. (Lecythidaceae family) and provided a sample to this study.…”
Section: Lup-20(29)-en-3-one (10)mentioning
confidence: 99%
See 1 more Smart Citation